Leaf extract of bryophyllum pinnatum: a potential tenderizer for goat meat - Maathumai, S.; Kapilan, R.; Arampath, P.C. (University of Jaffna, 2019)
Tenderness of the cooked goat (Capra aegagrus hircus) meat is one of the significant sensory attributes highly expected by the goat meat lovers in Sri Lanka. The leaf of Bryophyllum pinnatum is traditionally used as a meat tenderizer in Northern Province. The research objective was to determine the optimum concentration of Bryophyllum pinnatum leaf extract as a tenderizer for goat meat chunks. Aqueous extraction of Bryophyllum pinnatum leaves was obtained by boiling chopped leaves in distilled water at 40 O C for 24 hours. Goat meat chunks (50g) were treated with four levels of leaf concentrations (0.2, 0.4, 0.6 and 0.8 % w/v) and distilled water (control). The chunks were marinated at 4 O C for 24 hours and treated with salt (2% w/w) followed by thermal treatment at 121 O C for 15 minutes. pH and weight difference of the meat chucks were measured after thermal treatment. Sensory attributes of heat treated chunks were evaluated using Hedonic Scale (9 points) with 30 semi-trained panelists. pH value of meat chunks was significantly decreased with increasing concentration of leaf extract. While thermal yield of meat chunks increased significantly with increasing concentration. . Mean scores of sensory attributes, colour, flavor and juiciness of meat chunks did not show significant difference (n>0.05) compared to the control and increasing concentration of extract did not influence on them, but mean scores for overall acceptability and tenderness were higher than the control. Significantly highest mean scores for the overall acceptability values and tenderness were observed in 0.6 % and 0.8 % leaf extraction concentration than other treatments and both concentrations showed similar result in all the sensory attributes and thermal yield. In conclusion, 0.6 % (w/v) Bryophyllum pinnatum leaf extract was the optimum concentration for goat meat tenderization.